2015
DOI: 10.1152/ajpcell.00381.2014
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of basal promoter activity of the human thiamine pyrophosphate transporter SLC44A4 in human intestinal epithelial cells

Abstract: Microbiota of the large intestine synthesize considerable amount of vitamin B1 in the form of thiamine pyrophosphate (TPP). There is a specific high-affinity regulated carrier-mediated uptake system for TPP in human colonocytes (product of the SLC44A4 gene). The mechanisms of regulation of SLC44A4 gene expression are currently unknown. In this study, we characterized the SLC44A4 minimal promoter region and identified transcription factors important for basal promoter activity in colonic epithelial cells. The 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…An in silico CpG island prediction/primer design Methprimer algorithm [ 25 ] was used to predict the CpG islands in the promoter region of the SLC44A4 gene. Experimentally verified 1,022 bp SLC44A4 promoter [ 15 ] was subjected to prediction algorithm analysis using the default parameters. The analysis identified a single CpG island that was defined in accordance with the classical sequence parameters of the CpG islands [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An in silico CpG island prediction/primer design Methprimer algorithm [ 25 ] was used to predict the CpG islands in the promoter region of the SLC44A4 gene. Experimentally verified 1,022 bp SLC44A4 promoter [ 15 ] was subjected to prediction algorithm analysis using the default parameters. The analysis identified a single CpG island that was defined in accordance with the classical sequence parameters of the CpG islands [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies from our laboratory have shown that human colonocytes possess an efficient and specific carrier-mediated process for uptake of the microbiota generated TPP [ 13 ]. We have also established the molecular identity of the colonic TPP transporter (TPPT) as the product of the SLC44A4 gene [ 14 ], and have further cloned and characterized its 5’-regulatory region and showed an important role for the ETS/ELF3 (E74-Like Factor 3 (Ets Domain Transcription Factor, Epithelial-Specific)) and CREB-1 (cAMP-responsive element-binding protein-1) transcriptional factors in regulating the basal activity of the SLC44A4 promoter [ 15 ]. While examining the pattern of expression of the TPPT along the human and mouse GI tract, we found that expression of this system is mainly restricted to the colon with negligible expression in other parts of the GI tract [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This carrier consists of 710 amino acids and is highly expressed in epithelial cells of the colon, prostate, trachea, and lungs. TPPT has an important role in TPP absorption from microbiota and contributes to cellular nutrition of the local colonocytes …”
Section: Biochemistry Of Thiamine In Humansmentioning
confidence: 99%
“…TPPT has an important role in TPP absorption from microbiota and contributes to cellular nutrition of the local colonocytes. 28 The whole body content of thiamine is estimated in 25 to 30 mg, mostly located in skeletal muscles, heart, brain, liver, and kidneys. In the blood, 80% of thiamine is located in erythrocytes as TPP.…”
Section: Proteins Involved In Thiamine Transport and Metabolismmentioning
confidence: 99%
“…195 Indeed, human colonocytes express a thiamine pyrophosphate-specic transport that would allow for uptake of this vitamin by the host. 184,[197][198][199] Interestingly, variants in this gene have been identied as susceptibility markers for ulcerative colitis in Northern Indian populations, which are known to exhibit thiamine deciency. 200,201 This connection between thiamine uptake and ulcerative colitis remains to be explored further.…”
Section: Vitamin Biosynthesismentioning
confidence: 99%